The Hidden Costs of Ethnic Conflict : Decomposing Trends in Educational Outcomes of Young Kosovars - Alva, Soumya; Murrugarra, Edmundo; Paci, Pierella (World Bank, Washington, DC, 2014)
The authors examine the impact of ethnic segmentation in education on educational outcomes. Between 1991 and the late 1990s, the Albanian Kosovar population received education services in an informal system parallel to the official one. Using the 2000 Kosovo LSMS Survey data, the authors exploit cohort differences in exposure to the parallel system to estimate its effects among Albanian youth. The first (untreated) cohort includes individuals who entered secondary education before 1991 when the "parallel" education system was initiated. The second (treated) cohort includes individuals who entered secondary school in the last ten years under the ethnically segmented education system. To disentangle the effects of the changing system and economic environment, and the changes in the characteristics of the population, a Oaxaca-type decomposition is used. The results suggest that the past decade of ethnic tension has claimed a substantial toll on the educational outcomes of young male Albanian Kosovars. In addition to declines in enrollment rates in secondary education, those who are enrolled are expected to complete one less year of education. However, secondary school enrollment for girls increased during the parallel system, but with a sharp decline in the expected number of years completed.